Forsythoside A Modulates Zymosan-Induced Peritonitis in Mice - Zhang, Xiao-Tian (Molecules, 2018)
Acute inflammation is a protective response of the host to physical injury and invading infection. Timely treatment of acute inflammatory reactions is essential to prevent damage to organisms that can eventually lead to chronic inflammation. Forsythoside A (FTA), an active constituent of Forsythia suspensa, has been reported to have anti-inflammatory, antioxidant, and antibacterial properties. Despite increasing knowledge of its anti-inflammatory effects, the mechanism and the effects on acute inflammation are poorly understood. This study is aimed at exploring the pro-resolving effects of FTA on zymosan-induced acute peritonitis. FTA significantly alleviated peritonitis as evidenced by the decreased number of neutrophils and levels of tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6), and monocyte chemoattractant protein-1 (MCP-1) in the peritoneal cavity, without interfering with interleukin-10 (IL-10). FTA showed marked regulation of inflammatory cytokines and chemokine levels in zymosan-stimulated RAW 264.7 macrophages. Moreover, FTA could suppress the activation of NF-κB. In conclusion, FTA alleviated zymosan-induced acute peritonitis through inhibition of NF-κB activation.